Acute toxicity test of Rhizophora apiculata bark extract on rat liver and kidney histology using fixed dose method - Syazili Mustofa; Ilma Puteri Hutami; Dwi Sarwindah (Acta Biochimica Indonesiana, 2024)
Background: The therapeutic properties of the ethanol extract derived from the stem bark of Rhizophora apiculata have been investigated. Nevertheless, there is a lack of studies regarding its acute toxicity.